Human occupation of the northern Arabian interior during early Marine Isotope Stage 3. (November 2016) - Jennings, Richard P.; Parton, Ash; Clark‐Balzan, Laine; White, Tom S.; Groucutt, Huw S.; Breeze, Paul S.; Parker, Adrian G.; Drake, Nick A.; Petraglia, Michael D.
ABSTRACT: The early part of Marine Isotope Stage (MIS) 3 (ca. 60–50 ka) is a crucial period for studying human demography and behaviour in south‐west Asia, and how these relate to climatic changes. However, the archaeological and palaeoenvironmental records for MIS 3 in critical areas such as the Arabian Peninsula remain poorly developed. Here, we present findings from the Al Marrat basin in the Nefud desert, which provides the first clear evidence for both increased humidity and human occupation of the interior of northern Arabia during early MIS 3. A Middle Palaeolithic assemblage, dated by optically stimulated luminescence to ca . 55 ka, was found stratified within a sequence of relict palustrine deposits indicative of shallow water body formation in the Al Marrat basin. Hominin presence in northern Arabia at this time coincides with the intensification and northward displacement of monsoon rainfall systems during a period of maximum insolation. These findings add to a growing corpus of palaeoenvironmental evidence, which indicates that the Arabian interior was neither arid nor unpopulated during early MIS 3, and that hydrodynamic responses to enhanced moisture availability facilitated demographic expansions into the Arabian interior.